Production and evaluation of particleboard made of sawdust and sugarcane bagasse with polyurethane resin based on castor oil - Pivetta, Raissa Pravatta; Buzo, Ana Laura Soler Cunha; Sugahara, Estéfani Suana; Silva, Sérgio Augusto de Mello da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Among the goals for sustainable development in Brazil, studies have been conducted to better use of industrial and agricultural waste to promote adequate final disposal of these and generate new materials that minimize the exploitation and use of natural resources. In this work, the proposal is to make and evaluate boards with nominal density of 0.80 g.cm-3 using sugar cane bagasse, sawdust and polyurethane resin derived from castor oil. Thus, three treatments with different percentages of particles and 10% of PU-castor were proposed for the preparation of boards that were pressed with a pressure of 50 kgf.cm-2, a temperature of 100°C and a pressing time of ten minutes. The boards were evaluated for their physical properties (density, moisture content and swelling) and mechanical (static flexure and perpendicular traction) according to NBR 14810: 2-2013 and presented average values density of 936 to 937 kg.m-3, swelling after 24 hours of 5.0 to 7.2%, modulus of resistance to static bending of 22 to 23 MPa and perpendicular traction of 0.71 to 0.87 MPa. The results obtained with the tests indicate the great potential of use of sugarcane bagasse and sawdust to produce boards of high density particles.